To solve the quadratic equation \(3x^2 + 18x + 24 = 0\) using the quadratic formula, we start by identifying the coefficients:
- \(a = 3\)
- \(b = 18\)
- \(c = 24\)
The quadratic formula is given by:
\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \]
Now we substitute the values of \(a\), \(b\), and \(c\) into the formula.
- Calculate the discriminant (\(b^2 - 4ac\)):
\[ b^2 = 18^2 = 324 \] \[ 4ac = 4 \cdot 3 \cdot 24 = 288 \] \[ b^2 - 4ac = 324 - 288 = 36 \]
- Now substitute \(b\) and the discriminant into the quadratic formula:
\[ x = \frac{{-18 \pm \sqrt{36}}}{2 \cdot 3} \] \[ x = \frac{{-18 \pm 6}}{6} \]
- Now we find the two possible values for \(x\):
-
First, using the plus sign: \[ x = \frac{{-18 + 6}}{6} = \frac{{-12}}{6} = -2 \]
-
Second, using the minus sign: \[ x = \frac{{-18 - 6}}{6} = \frac{{-24}}{6} = -4 \]
Thus, the solutions are:
\[ x = -2 \quad \text{and} \quad x = -4 \]
Therefore, the correct response is:
x = -2, x = -4